KARAKTERISTIK DAN PENAFSIRAN PEMAKAIAN BAHASA DALAM BIDANG HUKUM - Purnanto, Dwi (Kajian Linguistik dan Sastra, 2006)
Foreign law system (especially the Dutch system) which is mostly used as the Indonesia law system has also influenced a typical use of the Indonesian language in law. The use of key terms, senteces, and the law discourse is closely related to its source. To interprete the language use in law; therefpre, one needs to know several strategies. The interpretation of language use in law may function to determine the meaning and purpose of law registers. Besides, the interpretation can also be done by determining the linguistic elements_phrases and claudes_as sentence former and by determining key words to indentipy the content of law discourse.Â Key words: law register, linguistic elements, teks, wacana hukum, dan KUHP.